'The Shapeless Ghost': Ambiguous Loss and Creativity in Learning How to Breathe - Robertson, Rachel (University of Canberra, 2013)
This paper explores the representation of ambiguous loss in a recent Australian memoir, Learning how tobreathe by Linda Neil (2009). My reading of this memoir focuses on the way presence and absence aremanifested in the text and the way acts of creativity— making music, recreating family history and writingthe memoir—are invoked as a way of tolerating ambiguity and reconfiguring the narrator’s sense ofidentity. I suggest that memoirs about ambiguous loss give an important voice to an otherwise silenced,though common, form of grief.